PRELIMINARY NOTES ON ISLAMIC POLITICAL SPACE: MADINA IN QUR’ANIC DISCOURSE - Ziada, Hazem (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2011)
Is there a particularly Islamic political space? This paper initiates this long-term research project of spatializing early Islamic history, drawing on the Qurâ€™Änâ€™s own spatial discourse. The project seeks to articulate the roles space plays in early Islamâ€™s political project. Within this framework, this paper defends the assertion that early Islam presents socio-political relationships which suggest al-madina â€“a particular conception of the â€˜cityâ€™ - as a pivotal locus in this formative political space. Arguments focus on the origins of such a conception in its Meccan Qurâ€™Änic occurrences. Four Â preliminary features emerge: the madinaâ€™s association with Qurâ€™Änic journey- narratives and debates of legitimate authority; its environmental connection to a productive hinter-land; its association with a trans-tribal social structure; and its evocation of a public-sphere. Set against the historical background of late-antiquity in which the first Muslim umma appeared and where concurrently the city, as a social artifact, faced threats of dispersion and irrelevance, these features potentially constitute a program for the emergent umma to salvage urbanity itself. In a later paper, evidence from the Prophetâ€™s acts in al-Madina (Yathrib) and his Companionsâ€™ developments of other urban settlements, especially al-Kufa, will be engaged to substantiate the relation between Qurâ€™Änic text and human action. Â Keywords: Â Qurâ€™anic verses, political space, Muslim umma, madina